Comportamento de compra dos consumidores num ambiente multicanal: o caso de um grande varejista brasileiro - Santana, Paulo (2015)
In recent decades, retail has undergone several transformations. In particular, after the popularization of the internet, the role of physical and virtual channels have changed. These changes had a direct affect on the customer purchase behavior, in that the customer has several points of contact with the retailer. The present study aims at refining, in the Brazilian context, the article by Schröder and Zaharia (2008) which analyses the guidelines of consumer purchases (Convenience, Independence, Recreation and Risk aversion) and how these guidelines influence the choice by consumers, research channels and purchase from a retailer. Through the case study, with a major multichannel Brazilian retailer, a survey was made with its consumers to assess how the guidelines for purchase influence behavior and the choice of the channel to be used. It is believed that with the obtained findings will contribute with the academy to understand the effect of guidelines for purchase in the consumer purchase behavior in this environment of transformation; and for the management, to collaborate with the retail sector demonstrating that the use of purchase guidelines in process improvements and development of contact channels consumers can positively affect the relationship, fulfilling consumers’ needs and increasing loyalty.